Experiencing e-assessment during COVID-19: an analysis of Indian students' perception - Arnab Kundu; Tripti Bej (Higher Education Evaluation and Development, 2021)
Purpose – Presently the whole world has been experiencing a pandemic threat of coronavirus diesease 2019 (COVID-19) and at the same time facing unprecedented changes in everything including education. E-learning has evolved as the only alternative of knowledge transmission even in third world nations, and e-assessment has been playing an increasingly important role in this digital transformation of education. But how far and of what depth it has made its place among students' minds need to be studied to leverage its full potential to transform students' learning needs. This study reports an investigation made in this direction. Design/methodology/approach – An online survey consisting of 40 questions in Google Forms was conducted to collect primary data on students' perception of e-assessment among 200 Indian students pursuing higher education from several geographical locations. The quantitative methodological approach was followed. The data were analyzed descriptively and inferentially. Findings – The results were analyzed based on the model of acceptance and usage of e-assessment (MAUE), and findings revealed that students' overall perception toward e-assessment was of moderate level and this perception varies depending on their gender, academic level, nature of the stream of study and their economic condition. Of the eight domains investigated, students showed better perception in the perceived usefulness, perceived ease of use, compatibility, subjective norms and self-efficacy domains, while they cut a sorry figure in domains like awareness, resource facilitation and information technology (IT) support. It became evident from their responses that COVID was instrumental in enhancing their interest in e-assessment. Social implications – The implication of this study lies in strengthening e-assessment by attending to the factors as noted in the MAUE in India and alike developing nations having huge space left for e-learning to reach a boom. Originality/value – This is an empirical investigation conducted in India on the state of students' perception of the e-assessment in the backdrop of the COVID-19 outbreak. To do this work, the authors conducted online surveys, and the write-up of the findings focus on the survey data only.